Plastome assembly and phylogenomics of Annonaceae subfamily Malmeoideae - Neo, Wei Ling (Nanyang Technological University, 2021)
The flowering plant family Annonaceae includes 111 genera and about 2450 species of trees, shrubs and lianas. It is a characteristic and species-rich element of lowland rainforests throughout the African, Asian, and New World tropics. The infrafamilial classification of Annonaceae has stabilised in the last decade and subfamiliar and intertribal relationships are relatively well understood, but there are some notable exceptions. The relationships of several tribes in subfamily Malmeoideae (~885 species) remain poorly understood, and the intergeneric relationships in tribe Miliuseae (~25 genera and ~620 species) remain poorly resolved. To address these problems, total genomic DNA and targeted enrichment libraries of 65 Malmeoideae accessions (~94% of the genera) were sequenced and plastome data were assembled using de novo assembly approaches. Likelihood and Bayesian phylogenetic analyses were used to infer hypotheses of phylogenetic relationships. The results largely resolve intertribal relationships in Malmeoideae and provide some new insights into intergeneric relationships in the recalcitrant tribe Miliuseae, but some backbone nodes remain only poorly supported. A literature survey summarizing observations of pollinators, flower sexuality and pollen dispersal units of Malmeoideae species is presented, the results are mapped on the plastome phylogeny, and the character distribution in the subfamily is discussed.